The Biology of Normal Zona Glomerulosa and Aldosterone-Producing Adenoma: Pathological Implications - Seccia, Teresa M (Endocr Rev, 2018)
The identification of several germline and somatic ion channel mutations in aldosterone-producing adenomas (APAs) and detection of cell clusters that can be responsible for excess aldosterone production, as well as the isolation of autoantibodies activating the angiotensin II type 1 receptor, have rapidly advanced the understanding of the biology of primary aldosteronism (PA), particularly that of APA. Hence, the main purpose of this review is to discuss how discoveries of the last decade could affect histopathology analysis and clinical practice. The structural remodeling through development and aging of the human adrenal cortex, particularly of the zona glomerulosa, and the complex regulation of aldosterone, with emphasis on the concepts of zonation and channelopathies, will be addressed. Finally, the diagnostic workup for PA and its subtyping to optimize treatment are reviewed.